Advanced Treatment of Pesticide-Containing Wastewater Using Fenton Reagent Enhanced by Microwave Electrodeless Ultraviolet. (11th August 2015) - Cheng, Gong; Lin, Jing; Lu, Jian; Zhao, Xi; Cai, Zhengqing; Fu, Jie
Abstract : The photo-Fenton reaction is a promising method to treat organic contaminants in water. In this paper, a Fenton reagent enhanced by microwave electrodeless ultraviolet (MWEUV/Fenton) method was proposed for advanced treatment of nonbiodegradable organic substance in pesticide-containing biotreated wastewater. MWEUV lamp was found to be more effective for chemical oxygen demand (COD) removal than commercial mercury lamps in the Fenton process. The pseudo-first order kinetic model can well describe COD removal from pesticide-containing wastewater by MWEUV/Fenton, and the apparent rate constant ( k ) was 0.0125 min −1 . The optimal conditions for MWEUV/Fenton process were determined as initial pH of 5, Fe 2+ dosage of 0.8 mmol/L, and H2 O2 dosage of 100 mmol/L. Under the optimal conditions, the reaction exhibited high mineralization degrees of organics, where COD and dissolved organic carbon (DOC) concentration decreased from 183.2 mg/L to 36.9 mg/L and 43.5 mg/L to 27.8 mg/L, respectively. Three main pesticides in the wastewater, as Dimethoate, Triazophos, and Malathion, were completely removed by the MWEUV/Fenton process within 120 min. The high degree of pesticides decomposition and mineralization was proved by the detected inorganic anions.